Strengthening People’s Politics According to the Principles of Buddhism in the Era of Disruption Mueang Khon Kaen District Khon Kaen - Mason, Chairat; (Nipon Tobkaew), Phrakhru Srisitthikankoson; Choutikavatchagul, Songphon; (Somsak Sinna), Phrakhru Pariyatchanbandit; Wasanthaweathi, Phramaha Wasan (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were: 1) to study the promotion of participatory politics based on Buddhist principles in the disruption era in Mueang Khon Kaen District, Khon Kaen Province, 2) to examine the development of participatory politics based on Buddhist principles in the disruption era, and 3) to propose guidelines for promoting participatory politics based on Buddhist principles in the disruption era. This study employed a qualitative research design using in-depth interviews. The participants were selected through purposive sampling, consisting of 26 individuals: Buddhist monks knowledgeable in Buddhist principles, political scholars, and local citizens in Mueang Khon Kaen District. Data were collected through interviews, questioning, and note-taking, and analyzed using descriptive content analysis. The research findings revealed that: 1) Promotion of participatory politics based on Buddhist principles in the disruption era: It was found that citizens still faced problems of political conflict, injustice, partiality, and self-interest among politicians, which undermined transparency and trust in the political system. 2) Development of participatory politics based on Buddhist principles in the disruption era: There have been efforts to improve politics in line with democracy, emphasizing citizen participation, equality, and the creation of a political culture grounded in morality and public interest. 3) Guidelines for promoting participatory politics based on Buddhist principles in the disruption era: The focus should be on cultivating political ethics among politicians, fostering unity and citizen engagement, and developing fair, transparent socio-political processes that genuinely respond to the needs of the people